Ethnomathematical Study on Indigenous Fish Trap: Example from Kijang, Bintan Regency - Febrian Febrian; Puji Astuti; Susanti Susanti (Jurnal Pendidikan Matematika, 2023)
The continuous exploration of mathematics as a human activity triggers the need to research ethnomathematics. This study aimed to identify ethnomathematics in the manufacture of indigenous fish traps (Bubu) from Bintan Regency. This ethnography study uses direct observation, interviews, and documentation. The researcher acts as the main instrument. The data were analyzed using the Spradley analysis technique, namely domain, taxonomic, componential, and cultural theme analysis. Data reduction, data presentation, and conclusions were carried out for each analysis. The results show that there are mathematical activities in designing, counting, and measuring length dimensions in Bubu's making. In these activities, there are mathematical concepts, including three-dimensional figures, the net of three-dimensional figures, curves, odd numbers, sequences with their attributes, bilateral symmetry, symmetry axes, figurative numbers, the congruence of plane figures, and length measurements with non-standardized units. These results showed that the Bubu maker already had a geometric sense through the symmetrical concept that became the basis for two activities such as counting and measuring, similar to the results of ethnomathematical research on the Yupiaq Eskimo community in Alaska and the Carolina Islanders in Micronesia. This study provides ideas to utilize everyday phenomena in teaching mathematics as a starting point prior to learning mathematics more formally.